VALIDASI METODE ANALISIS KADAR TIMBAL (Pb) DALAM MADU ALAM DI KALIMANTAN TIMUR - Finqo Aprianto; Bohari Yusuf; Rahmat Gunawan (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2012)
Analysis method for determining Pb content in natural honey have been developed and validated. Research was done by analyzing one natural honey sample collected from Teritip (Balikpapan) with standard analysis method and three developed analysis method which their analytical performance tested later. Pb content was determined with atomic absorption spectrometry after dry digestion (method A) or wet digestion (method B (HNO3-H2O2; 3:8), C (HNO3-H2O2; 2:1) and D (HNO3)). Analytical performance parameter e. G. Linearity, working range, limit of detection, limit of quantitation, precision and accuracy were tested. Content of Pb in natural honey sample which analyzed with method A, B, C and D were found at 0.7923 ± 0.0311 µg/g, 0.7944 ± 0.0216 µg/g, 0.7998 ± 0.0218 µg/g and 0.7912 ± 0.0160 µg/g respectively. Analytical performance of four tested analytical method were still acceptable. Significance testing result showed that there were no significant differences in precision and accuracy between developed analysis method and standard analysis method, execpt for method D. Precision of method D was significantly better than standard analysis method.Keywords: Honey, Lead, Method Validation